SIDDHA SYSTEM OF MEDICINE: A REVIEW OF BASIC CONCEPTS AND EVIDENCE-BASED HERBAL REMEDIES FOR RESPIRATORY DISEASES. - B. Shalini; K. Suresh; M. Meenakshi Sundaram (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Purpose of ReviewThe Siddha system is one of the oldest medical traditions, and it is mainly used in southern India. It possesses a vast library of classical literature in addition to a variety of herbal remedies that are remarkably effective in preventing and treating respiratory diseases. The purpose of this review is to evaluate the Siddha system of medicine and Siddha pharmacology and to evaluate the effectiveness of herbs and Siddha formulation ingredients for the symptomatic treatment of respiratory diseases.Recent FindingsAs per Siddha literature Fundamental Principles of Siddha system of medicine include theories of Five Elements (Panchaboothams), and Three humors (Uyir thathukkal) and Siddha pharmacology is used to determine diagnosis, aetiology, treatment and prognosis. Siddha medicinal herbals and formulations possessing particularly against respiratory disease are elaborated. Evidence of anti-viral properties has been brought to light for further clinical trials. Preclinical and clinical research are covered in this review article to provide a scientific basis for formulations that are frequently employed in the Siddha medical system.SummaryRespiratory diseases that are spreading quickly throughout the world, are major health issues. The current treatment has significant side effects in addition to its own shortcomings. The need to find a safer alternative therapy to treat these epidemic diseases is critical. In this review, we have given an overview of the most common respiratory illnesses, given a brief description of the Siddha system of medicine and Siddha pharmacology, and categorized a class of plants and formulation from this system that are frequently used to treat respiratory illnesses.